NF-ΚB-Induced Upregulation of miR-548as-3p Increases Invasion of NSCLC by Targeting PTEN - Akgun, Sakir; Kucuksayan, Hakan; Ozes, Osman N.; Can, Ozge; Alikanoglu, Arsenal S.; Yildiz, Mustafa; Akca, Hakan (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: Non-Small Cell Lung Cancer (NSCLC) is an aggressive cancer type due to high metastatic capacity. Nuclear Factor Kappa B (NF-ΚB) is a consistently active transcription factor in malignant lung cancer cells and has crucial significance in NSCLC progression. It is also implicated in the transcriptional regulation of many genes including microRNAs (miRNAs) that function as tumor suppressor or oncogene. It has been increasingly reported that several miRNAs defined as gene members are induced by NF-ΚB. The present study aimed to find novel miRNAs that are regulated by NF-ΚB. Methods: Chromatin İmmunoprecipitation Sequencing (ChIP-Seq) experiment and bioinformatic analysis were used to determine NF-ΚB-dependent miRNAs. Western blot analysis, quantitative real-time polymerase chain reaction (qRT-PCR), luciferase reporter gene assays were carried out to investigate the target genes of miRNAs. To determine biologic activity, transwell invasion and MTT assay were carried out on H1299 NSCLC cell line. miRNA expression level was evaluated in metastatic and non-metastatic tissue samples of NSCLC patients. Results: ChIP-Seq and qRT-PCR experiments showed that miR-548as-3p is transcriptionally regulated by NF- ΚB in response to Tumor Necrosis Factor-α (TNF-α) treatment. Then, we found that tumor suppressor Phosphatase and Tension homolog (PTEN) is a direct target of miR-548as-3p. Furthermore, miR-548as-3p mediates phosphatidylinositol-3-OH kinase (PI3K)/Akt pathway and NF-ΚB-implicated genes including Matrix Metalloproteinases 9 (MMP9), Slug and Zeb1. We further showed that miR-548as-3p increased invasiveness of NSCLC cells and was upregulated in metastatic tumor tissues compared to non-metastatic ones. Conclusion: All these findings provide a miRNAs-mediated novel mechanism for NF-ΚB signaling and that miR-548as-3p could be a biomarker for NSCLC metastasis.
Keywords: neoplasm metastasis